Controller design for two-wheels inverted pendulum mobile robot using PISMC - Nawawi, Sophan Wahyudi; Ahmad, Mohamad Noh; Osman, Johari Halim Shah; Husain, Abdul Rashid; Abdollah, Mohd. Fairus (2006)
The research on two-wheel inverted pendulum or commonly call balancing robot has gained momentum over the last decade in a number of robotic laboratories around the world. This paper deals with the modeling of 2-wheels Inverted Pendulum and the design of proportional integral sliding mode control (PISMC) for the system. The mathematical model of 2-wheels inverted pendulum system which is highly nonlinear is derived. The final model is then represented in state-space form and the system suffers from mismatched condition. A robust controller based on sliding mode control is proposed to perform the robust stabilization and disturbance rejection of the system. A computer simulation study is carried out to access the performance of the proposed control law.